Management of Records and Clients Satisfaction at Magistrate Court at Kabale. - Atukwase, Sarah Loynet (Kabale University, 2023)
The purpose of the study was to find out records management and clients' satisfaction in Magistrate Court, Kabale. The study was guided by objectives of the study; to identify the different types of records managed at Magistrate Court, Kabale and to find out the users satisfaction with records kept at Magistrate Court, Kabale. The researcher selected a sample of # ,· .. . 25 respondents who reresented the whole study population using purposive sampling, 5 staff members from records department and 20 users were selected. Data was then analyzed for easy interpretation and understanding. The findings from the study revealed that tere were several types of records generated at Magistrate Court, Kabale and among others include, administration and withdrawal register record, financial records, and administrative records. It was concluded that customer satisfaction with the current records was inefficient and does not effectively support public service delivery. This was evidenced by the fact that there was no awareness and existence of the records management policy, procedures manual and service standards from the Magistrate Court, Kabal.e. This resulted in an ineffective records management programme. It was concluded that customer satisfaction with the current records was inefficient and does not effectively support public service delivery. This was evidenced by the fact that there was no awareness and existence of the records management policy, procedures manual and service standards from the Magistrate Court, Kabale. Electronic filling should be embraced. This includes keeping files in soft copy devices as well as computers tapes, flash disks and computer disks. The researcher also recommends that records staff should be given their computers connected to internet to store confidential information about the Magistrate court here the researcher based on the fact that a lot of records are kept in personal computers